Is there a Place at the Adult Education Table for Positive Psychology?: Theorizing from the Literature - Michelle N. Anderson; Ralph G. Brockett (Adult Education Research Conference, 2008)
The purpose of this paper is to address the potential relationship that could be established between adult education and positive psychology by understanding the foundation, possible contradictions, and concerns of positive psychology.
Keywords: adult learning; positive psychology; educator feedback